2005
DOI: 10.1038/sj.leu.2403945
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of myelodysplastic syndromes: a case–control study

Abstract: Little is known about the etiology of myelodysplastic syndromes (MDS) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
105
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 39 publications
5
105
1
2
Order By: Relevance
“…35 Strom et al could show a joint effect between smoking and chemical exposure with the highest risk among smokers exposed to solvent/agricultural chemicals. 31 Recently, Sekeres described advanced age, male gender, smoking and previous exposure to chemotherapy, radiation therapy or exposure to industrial chemicals as the most common risk factors for developing MDS. 36 In our study, no significant differences in dysmyelopoiesis could be attributed to smoking habits.…”
mentioning
confidence: 99%
“…35 Strom et al could show a joint effect between smoking and chemical exposure with the highest risk among smokers exposed to solvent/agricultural chemicals. 31 Recently, Sekeres described advanced age, male gender, smoking and previous exposure to chemotherapy, radiation therapy or exposure to industrial chemicals as the most common risk factors for developing MDS. 36 In our study, no significant differences in dysmyelopoiesis could be attributed to smoking habits.…”
mentioning
confidence: 99%
“…Myelodysplastic syndrome is a heterogeneous clonal haematological disorder that can progress to AML. Cigarette smoking (Nisse et al, 2001), solvent exposure (Nisse et al, 2001) and agricultural exposures (Strom et al, 2005) have all been associated with an increased risk of MDS, and senescence of the haematopoietic system is thought to play a role in its development (Dalamaga et al, 2002). Less is known about the causes of MPDs, including polycythemia vera and essential thrombocythemia.…”
mentioning
confidence: 99%
“…Although the exact link between alcohol and MDS is not yet clear, it is reported that alcoholics induce chromosomal abnormalities in hematopoietic cells with altered gene expression patterns and adverse effects on the immune system [9,10,11]. Tobacco products like cigarettes which contain benzene and other carcinogens also induce chromosomal aberrations in primitive bone marrow cells leading to development of MDS [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These genetic abnormalities occur due to previous exposure to mutagens like benzene, alkylating agents, gasoline, topoisomerase II inhibitors, radiation etc. [7][8][9][10][11][12][13]. Due to exposure to insecticides, pesticides and herbicides agricultural workers are reported to have higher incidence of developing MDS [7].…”
Section: Introductionmentioning
confidence: 99%